Pencegahan Perundungan Masyarakat Terhadap Disabilitas - Azka Najmi; Naila Siti Wulandari; Neila Zira Alfiyah; Risti Prafitri; Siti Hamidah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Bullying, especially against individuals with disabilities, is a social issue that cuts across multiple spheres of life. Disability is often a source of inequality and discrimination, with vulnerable individuals being subjected to insensitive and harmful treatment. To create an inclusive and equitable environment, it is important for society to understand and prevent bullying of individuals with disabilities through awareness-raising and concrete actions.The literature review method used in the research on preventing bullying of individuals with disabilities is that this approach allows for the collection of relevant and high-quality information. By identifying the topic, conducting a source search, selecting sources based on inclusion criteria, analyzing the sources, and drafting the report, the researcher can produce a comprehensive and in-depth report on the topic. that a good understanding of disability, strong legal protection, an inclusive environment, and the involvement of all parties in society are key in preventing bullying of individuals with disabilities.